The Effect of NPF, BOPO, and FDR on the Profitability (ROA) of Bank NTB Syariah - Atkiyan, Fahrul Hudatil (Business Management, 2025)
Islamic banking plays an important role in promoting national economic development, particularly through fund collection and financing activities based on Islamic principles. In promoting sound economic development, Islamic banking must certainly increase its profitability. This study attempts to examine the factors that influence the profitability of Islamic banks, more specifically Bank NTB Syariah, which is the focus of this study. The results of this study found that NPF and Bopo did not have a significant effect on the profitability (ROA) of Bank NTB Syariah. However, the BOPO variable did have an effect on ROA, albeit a negative one.